Kumarakuruparar aruḷiya Nītineṟi viḷakkam : mūlamum uraiyum : Āṅkila moḻipeyarppum - Kantaiyā Piḷḷai, Na. Ci (SAMP early 20th-century Indian books project, 1949)
Commentary on Nītineṟi viḷakkam, Tamil didactic poetry, by Kumarakurupara Aṭikaḷ, 17th century Tamil poet and Śaivite leader.